Impact of rural-urban migration in low-income settlements in Bangladesh: A case study on Baganbari slum - Faeique, Azmaine (Universitas Airlangga, 2024)
Rural-urban migration is one of the most familiar terms in the present world, especially in developing countries. The people of Bangladesh have a strong tendency to migrate towards the megacities. The migrants are required to cope with many uncertainties, risks, and challenges. This paper is aimed to find out the impact of RUM especially on the life standards of the migrants. Here qualitative approach has been followed, and the Baganbari slum of Mirpur region has been selected as the representative of the slums of Bangladesh. Demographic characteristics of the respondents were presented here in order to categorize the migrants. Based on survey questionnaires, 20 household heads of the slum were part of the survey. Three key informant interviews, five FGDs, and two case studies were also used to collect data. During FGD and KII, the respondents were asked about their monthly income, hometown, religion, age, monthly income, and others. Also, the respondents mentioned about some causes of their migration. The study shows the brutalities of slum life and reflects the limitations of slum life as well. According to the findings of the study, the government should take a special look at the proper education and skill development facilities of the slum children.